Screening and Improving the Recombinant Nitrilases and Application in Biotransformation of Iminodiacetonitrile to Iminodiacetic Acid - Liu, Zhi-Qiang; Baker, Peter James; Cheng, Feng; Xue, Ya-Ping; Zheng, Yu-Guo; Shen, Yin-Chu (PLOS ONE, 2013)
In this study, several nitrilase genes from phylogenetically distinct organisms were expressed and purified in E. coli in order to study their ability to mediate the biotransformation of nitriles. We identified three nitrilases: Acidovorax facilis nitrilase (AcN); Alcaligenes fecalis nitrilase (AkN); and Rhodococcus rhodochrous nitrilase (RkN), which catalyzed iminodiacetonitrile (IDAN) to iminodiacetic acid (IDA). AcN demonstrated 8.8-fold higher activity for IDAN degradation as compared to AkN and RkN. Based on homology modeling and previously described ‘hot spot’ mutations, several AcN mutants were screened for improved activity. One mutant M3 (F168V/L201N/S192F) was identified, which demonstrates a 41% enhancement in the conversion as well as a 2.4-fold higher catalytic efficiency towards IDAN as compared to wild-type AcN.